Microglia Polarization with M1/M2 Phenotype Changes in rd1 Mouse Model of Retinal Degeneration - Zhou, Tian; Huang, Zijing; Sun, Xiaowei; Zhu, Xiaowei; Zhou, Lingli; Li, Mei; Cheng, Bing; Liu, Xialin; He, Chang (Frontiers in Neuroanatomy, 2017)
Microglia activation is recognized as the hallmark of neuroinflammation. However, the activation profile and phenotype changes of microglia during the process of retinal degeneration are poorly understood. This study aimed to elucidate the time-spatial pattern of microglia distribution and characterize the polarized phenotype of activated microglia during retinal neuroinflammation and degeneration in rd1 (Pde6brd1/rd1) mice, the classic model of inherited retinal degeneration. Retinae of rd1 mice at different postnatal days (P7, P14, P21, P28, P56 and P180) were prepared for further analysis. We found most CD11b+ or IBA1+ microglia expressed Ki-67 and CD68 in rd1 mice and these cells migrated towards the layer of degenerative photoreceptors at the rapid rods degeneration phase from P14 to P28. These microglia exhibited typical ameboid activated shape with round bodies and scarce dendrites, while at late phase at P180, they displayed resting ramified morphology with elongated dendrites. Flow cytometry revealed that the percentage of CD86+CD206- M1 microglia increased markedly in rd1 retinae, however no significant change was observed in CD206+CD86- M2 microglia. Interestingly, CD86+CD206+ microglia, an intermediate state between the two extremes of M1 and M2, increased markedly at the rapid rods degeneration phase. The immunofluorescence images revealed that microglia in rd1 mice highly expressed M1 markers including CD16/32, CD86, and CD40. In addition, increased expression of pro-inflammatory cytokines (TNF-a, IL-6 and CCL2) was observed in rd1 mice. Our findings unfolded a panorama for the first time that microglia conducted distinctive behaviors with the progression of retinal degeneration in rd1 mice. Microglia is activated and particularly polarized to a pro-inflammatory M1 phenotype at the rapid rods degenerative phase, suggesting that the involvement of M1 microglia in the retinal neuroinflammation and degeneration. Most microglia adopted an intermediate polarization ‘‘M1½’’ state in rd1, revealing that microglia orchestrated a complicated continuous spectrum in degenerative retina.